Behavioral Parent Training for Preschool ADHD: Family-Centered Profiles Predict Changes in Parenting and Child Outcomes. Issue 5 (3rd September 2022) - Dale, Chelsea; Parent, Justin; Forehand, Rex; DiMarzio, Karissa; Sonuga-Barke, Edmund; Long, Nicholas; Abikoff, Howard B.
ABSTRACT: Objective: Behavioral parent training (BPT) is the first line of treatment for preschool-aged children with attention-deficit hyperactivity disorder (ADHD); however, clinically significant improvements are not universal. In the current study, we employ a person-centered approach to create subgroups of families based on the intersection of multiple parent, child, and family pre-treatment factors. Further, we explore the utility of pre-treatment family profiles in predicting post-treatment differences in observed parenting behavior (i.e., behavioral control, parental warmth) and clinically significant change in child ADHD and oppositional symptoms. Method: Longitudinal data were collected using observational and parent-, teacher- and clinician-reported assessments from 130 parent-child dyads ( M age= 3.57, range = 3.0– 4.11, 73.8% male, 69.2% White, 25.6% Hispanic) participating in BPT. Results: Findings from the current study suggest three distinct family profiles, which consisted of one profile with high family stress (HFS) as evidenced by elevated symptomatology across parent, child, and family-level domains, a second profile with elevated parental anxiety (PA), and a final profile with elevated parental depression (PD). These family-centered profiles were differentially associated with changes in observed parenting practices. Specifically, the PD profile (39%) demonstrated minimal improvements in behavioral control and warmth following treatment. In contrast, the HFS profile (30%) only improved in behavioral control and the PA profile (31%) improved in both parenting domains following treatment. In addition, marginally significant differences in child oppositional and ADHD symptoms were observed across profiles. Conclusions: Family-centered approaches may be useful for selecting and implementing interventions.